Medium-term effect of fertilizer, compost, and dolomite on cocoa soil and productivity in Sulawesi, Indonesia - Fungenzi, Thomas; Sakrabani, Ruben; Burgess, Paul J.; Lambert, Smilja; McMahon, Peter; Fungenzi, Thomas (Cambridge University Press, 2021)
In Indonesia, management practices that reduce soil fertility could be limiting cocoa (Theobroma cacao L.) production. To address this, we investigated the effects of fertilizers and organic amendments comprising different combinations of NPK + urea, dolomite, and manure-based compost on soil properties and cocoa productivity. We extended an existing field experiment in South Sulawesi, Indonesia, to assess these treatments’ effects on cocoa trees from the age of 2.9 years to 7.4 years. The treatments were first applied 5 months after planting and subsequently twice a year. Soil analyses were performed before planting, after 3 years, and finally after 7 years. Productivity was assessed yearly between the age of 3.5 and 7.4 years. The highest yields were obtained from the plots receiving compost, although the yield benefits diminished over time. Inorganic fertilizer alone doubled the yield compared to the control, while the yields with compost and compost + fertilizer were three times that of the control. With dolomite alone, the yield cumulated over 4 years was 41% higher than the control. The positive effect of compost on cocoa yields can potentially be attributed to (1) physical changes increasing soil water availability, (2) the chemical improvement of nutrient availability, and (3) biologically, by promoting the activity of beneficial organisms. The application of dolomite increased soil pH, Ca, and Mg contents. Soil organic carbon greatly declined in the composted treatments, even though 10 kg of compost was applied per tree per year, probably because of the low C:N ratio of the compost. Future studies should assess different fertilizer formulations and combinations with organic inputs and explore the mechanisms by which compost promotes cocoa productivity.
Keywords: Cocoa; Soil fertility; Compost